The factors influencing farmers’ choice of improved maize seed varieties in Tanzania (International Journal of Scientific Research and Management (IJSRM), 2018)
The study examined the factors that influence farmers’ choice of improved maize seed variety in Tanzania. Using purposive sampling data were collected from 930 households. The binary logistic regression model was used to choose respondent who had used improved maize seed from all seven agro-ecological zones of Mainland Tanzania. The results showed that agro-ecological zones, farm size, household size and yield positively influence the likelihood of farmers’ choice of improved maize seed varieties. Based on these findings, it is recommended that researchers and suppliers of seed should consider the attributes of farmers’ preference in the production of improved maize seeds and put more emphasis on facilitating the delivery of agricultural extension services for more effective uptake of agricultural technologies